Intersexual relationships in mandrills: dominance, sexual conflict and the influence of social integration - Nikolaos Smit (Revue de Primatologie)
The conflict of evolutionary interests between the sexes is commonly imprinted in social dynamics and physical asymmetries between the sexes. In species that live in polygynandrous groups, male-biased sexual size dimorphism often allows males to socially dominate and sexually coerce females. Yet, smaller female size might allow females to escape from males and female philopatry might promote female-female social support allowing females to resist or retaliate against males. The study of such intersexual conflicts is highly relevant in mandrills (Mandrillus sphinx) as they form large polygynandrous groups and exhibit extreme male-biased sexual dimorphism in size and ornaments, higher social integration of females than males, and female coalitions against males. The set up of Mandrillus Project over a decade ago has offered a unique opportunity to study intersexual relationships of mandrills in their natural habitat. Here, I present a synthesis of some recent studies that used the long-term behavioural and life-history dataset of Mandrillus Project and documented patterns of sexual coercion and intersexual dominance in mandrills. These studies show that male mandrills are generally dominant over females and use sexual coercion to increase their mating success. However, female social bonds and social integration permit females to occasionally outrank certain males. Finally, and surprisingly, higher-ranking and more socially integrated females receive higher rates of male sexual coercion, highlighting the need for future research to shed light on the trade-offs between costs and benefits of mandrill sociality.